Pengaruh Pengetahuan, Kelompok Referensi Dan Motivasi Konsumen Terhadap Alasan Nasabah Menabung Di Bank Syariah Indonesia Jakarta Selatan - Ramadhan Putra Pratama; Sri Muljaningsih (Pusat Riset dan Inovasi Nasional, 2023)
In the world of banking in Indonesia, Islamic banking is a type of activity based on sharia principles that is free from usury. Unlike conventional banks which use interest in collecting and channeling funds, Islamic banks use financing as a contract. In conventional and Islamic banking there are differences in terms of banking operations. Therefore, this study aims to analyze the effect of knowledge, reference groups, and consumer motivation on customers' reasons for saving at Bank Syariah Indonesia, South Jakarta. The approach used in this research is a quantitative approach. The quantitative approach aims to determine the magnitude of the analyzed variables. The results of the study show that the knowledge variable and the consumer motivation variable do not have a significant influence on a person's decision to save at Bank Syariah Indonesia. Meanwhile, the reference group variable has a significant influence on a person's decision to save at Bank Syariah Indonesia, so that simultaneously high and low knowledge, reference group, and motivation if simultaneously have an influence on customers to save at Bank Syariah Indonesia.